Answers

  • Brainly User
2015-03-05T19:19:05+05:30
In triangle ABN,
as L is the midpoint of AB and lm is parallel to BN .
therefore M is the Midpoint of AN
Now,
AN=2CN(GIVEN)-equation(1)
Here,
as M is the mid point of AN.
Therefore AN=2AM-equation(2)
Now,From equation (1) and (2)
(AN=2CN)=(AN=2AM)
Therefore AM=CN
                              Hence proved
PLzzzzzzzzzzzzzzz MARK AS THE BEST ANSWER
PLZZZZZZZZZZZZZZZ
 


1 5 1
2015-03-06T11:24:32+05:30
In triangle ABN, as L is the midpoint of AB and lm is parallel to BN . therefore M is the Midpoint of AN Now, AN=2CN(GIVEN)-equation(1) Here, as M is the mid point of AN. Therefore AN=2AM-equation(2) Now,From equation (1) and (2) (AN=2CN)=(AN=2AM) Therefore AM=CN Hence proved
1 5 1